Texturização superficial de cilindros automotivos - Silva, Leonardo Rosa Ribeiro da (2016)
Surface texturing is an important tool to be used for reduction of the friction force in lubricated contacts, being its effectiveness evidenced in simulations and experimentally. A major barrier to use surface texturing in an industrial scale is the difficulty of finding application methods of these surface patterns that combine both high speed and low cost, thus making the surface texturing a more competitive technique. The objective of this work is to investigate the potentiality of inserting surface textures on the inner surface of an automotive cylinder liner made of grey cast iron, using Maskless Electrochemical Texturing Method (MECT), which is a both low cost and high-speed texturing process. Once established the texturing parameters for the method MECT for the grey cast iron, were made Block-on-Ring tests to compare the improvement in reducing friction force and wear of the textured samples in comparison with samples mechanically and electrochemically polished. The method MECT proved to be a viable method for texturing of automotive cylinder liners, being both fast and low cost. In the Block-on-Ring tests, the texturized samples showed lower friction coefficient and wear volume compared to the mechanically and electrochemically polished samples.